Chronic uterine inversion in a nulligravida female: an extremely rare case - Arora, Navidha; Jodha, B. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Chronic non-puerperal uterine inversion is an extremely rare gynecological condition in which the uterine fundus turns inside out through the cervix. It usually occurs secondary to benign uterine pathology and is exceptionally uncommon in nulligravid women. The condition often presents with a chronic course and vague symptoms, leading to delayed diagnosis and treatment. A 22-year-old nulligravid woman presented with a seven-year history of a gradually enlarging vaginal mass, pelvic heaviness, and irregular spotting. She had no history of prior pregnancies, surgeries, or systemic illness. Examination revealed a patulous cervical os with the uterine fundus seen protruding through it. Laboratory evaluation showed severe anemia (hemoglobin 4.2 g/dl) with otherwise normal parameters. Pelvic ultrasonography demonstrated the uterine fundus prolapsed into the cervical canal, and magnetic resonance imaging (MRI) confirmed chronic uterine inversion with a characteristic “cup-shaped” appearance. After correction of anemia with four units of whole blood and supportive therapy, laparotomy with an anterior cervical constricting incision (Haultain-type) was performed. The uterus was successfully reinverted and anatomically restored. Postoperative recovery was uneventful, and the patient was discharged on the fifth postoperative day with complete resolution of symptoms. Chronic non-puerperal uterine inversion should be considered in women presenting with a long-standing vaginal mass and bleeding. MRI plays a crucial role in diagnosis. Timely surgical correction after preoperative optimization provides excellent anatomical restoration and preserves future reproductive potential.